(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the specific features of pedagogical research and the stages of its organization. It has been revealed that the methodology of organizing pedagogical research, identifying evidence, evaluating, drawing approximate conclusions, and theoretical generalization is the main criterion in pedagogical research.